Inovasi Layanan Perizinan Keliling Online Cepat Untuk Semua (LAPAK OCU) di Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Kampar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
LAPAK OCU is an innovation by the Investment and One-Stop Integrated Service Office (DPMPTSP) of Kampar Regency designed to expand licensing access, particularly for business actors in remote areas. This study applies a qualitative method using Everett M. Rogers’ diffusion of innovation theory to assess relative advantage, compatibility, complexity, trialability, and observability. Data were collected through interviews, observations, and documentation. The results show that LAPAK OCU effectively accelerates business legalization, broadens service coverage, and increases public awareness of the importance of permits, as seen in the rise of issued licenses and socio-economic impacts. However, implementation is still constrained by limited internet connectivity, low digital literacy, and shortages in facilities and human resources. The study recommends strengthening digital infrastructure and enhancing staff capacity to ensure the sustainability and inclusiveness of this innovation.